Bacteriophage cocktail as a substitute for antibiotic-type growth promoters in poultry - Honorio-Javes, C. E. (2021)
Aviculture is forced to find alternatives to replace antibiotic-type growth promoters to reduce antimicrobial resistance. Among these alternatives we have bacteriophages that are the natural predators of bacteria; however, research point out to their use as therapeutics and not as growth promoters. For this reason, this review article focuses on discussing and projecting the use of lithic bacteriophage cocktails as growth promoters in commercial breeding of broilers, laying hens and quails. Evaluating its effects on production parameters, its application in drinking water and food, phage protection strategies on gastrointestinal pH changes and high pelleting temperatures, strategies against phage-resistance, its effects on the intestinal microbiota, and the use of autophages versus commercial products. It is concluded that the optimal use of bacteriophages in aviculture is through mixed cocktails of protected lithic autophages. Finally, it is recommended to compare the use of mixed lithic autophage cocktails with mixed commercial phage cocktails that exist on the market; Additionally, the combination of mixed cocktails of protected lithic autophages with other alternatives such as probiotics, prebiotics, essential oils and organic acids should be evaluated, and this combination should be compared with the use of growth-promoting antibiotics.